Overview of Chronic Energy Deficiency (CED) in Pregnant Women Based on Demographic Factors, Knowledge and Social Support - Armini, Ni Ketut Alit; Hasanah, Umi Nafiatul; Kurnia, Iqlima Dwi; Triharini, Mira (International Journal of Psychosocial Rehabilitation, 2020)
Chronic Energy Deficiency (CED) is the leading cause of maternal death. Pregnant women with poor nutritional status can cause CED. The purpose of this study was to determine the correlation between demographic characteristics, knowledge, and social support with chronic energy shortages in pregnant women. This study used a cross-sectional design. The population is pregnant women at the Tanah Kali Kedinding Public Health Center. The total sample of 186 respondents was taken by simple random sampling technique. The independent variables in this study were demographic characteristics (age, pregnancy distance, number of births, education level, employment status, income), knowledge and social support, while the dependent variable is the incidence of CED in pregnant women. Data were obtained by questionnaire and UAP measurement and analyzed using a chi-square test. There was a correlation between demographic factors based on age (p = 0.002), number of births (p= 0.012), pregnancy distance (p = 0.015), occupation (p=0.025) with CED in pregnant women, but there was no relationship educational factors (p= 0.444) and family income (p = 0.801). There is a relationship between knowledge (p=0.015) and social support (p=0.023) with CED in pregnant women. Demographic characteristics, knowledge, and social support have important contributions to the chronic lack of energy in pregnant women. It is important to provide counselling and assistance to pregnant women to increase awareness about fulfilling nutrition. Further experimental research needs to be done by providing interventions to overcome chronic energy deficiency in pregnant women.